The Dynamic Relationship between Globalization and Economic Growth: Its Implication on Business Policy - Rima Midiyanti; Ming Hung Yao (Jurnal Internasional Penelitian Bisnis Terapan, 2019)
The purpose of this study is to investigate the relationships between globalization and economic growth in Indonesia. Three globalization indices, economic globalization index, social globalization index and political globalization index, are used to measure the globalization. Johansen’s (1988) cointegration approach is used to estimate the model by using annual data from 1980 to 2014. The results indicate that there is a long-run cointegration relationship between globalization and economic growth in Indonesia. Globalization stimulates Indonesian economic growth in the long run. Meanwhile, political globalization implies short-run effect on the economic growth in Indonesia. From the policy perspective, this results support the argument that the government should take the international integration policy to sustain long-run economic growth.